Justice, entitlement and inheritance : exploring theoretical grounds for the rectification of manifest injustices through an analysis of inheritance - Spies, Frances (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)--Stellenbosch University, 2013.